Homozygous Novel Variants in the Glycine Decarboxylase Gene Associated with Nonketotic Hyperglycinemia in a Distinct Population - Elabd, Heba Salah Abdelkhalek; Bastaki, Fatma; Khalifa, Mohamed (Journal of Pediatric Genetics, 2021)
Glycine encephalopathy (GE), also known as nonketotic hyperglycinemia (NKH) is an autosomal recessive disorder due to a primary defect in the glycine cleavage enzyme system. It is characterized by elevated levels of glycine in the plasma and cerebrospinal fluid (CSF) and increased CSF to plasma glycine ratio.Mutations in three genes of the mitochondrial glycine cleavage system have been found to cause NKH. Most patients have a mutation in the GLDC.In this report, we present five new patients from Middle Eastern families with NKH. They were all born to consanguineous parents and two of them have family history of similarly affected sibling(s). All patients presented with neonatal encephalopathy associated with seizures. Their diagnoses were suspected clinically and confirmed biochemically.DNA sequence analysis of the five patients revealed five different pathogenic or likely pathogenic variants in the GLDC. Three were missense variants (c.2675C > T; p.Ala892Val), (c.2512A > G; p.Asn838Asp), and (c.2943A > C; p.Lys981Asn); one was an intronic missense variant (c.1402–2A > T) leading to an exonic deletion, and one was a deletion of 42 amino acids (c.1927-?_2052 + ?del.) All variants were novel and homozygous. The pathogenicity of these variants was determined according to the American College of Medical Genetics (ACMG) variant classification and in silico analysis. Another novel homozygous variant (c.1384C > G; p.Leu462Val) was detected, which was classified as likely benign.The novel variants identified in the GLDC in these patients underlie the pathogenesis of NKH, specifically for the Middle Eastern population. This expands the mutation spectrum of NKH to include a distinct ethnic population that has not been studied before.
Keywords: glycine encephalopathy; nonketotic hyperglycinemia; GLDC variants; ethnic population; Middle East population